Characterization of materials' elasticity and yield strength through micro-/nano-indentation testing with a cylindrical flat-tip indenter. Issue 4 (6th February 2015) - Hu, Zhong; Lynne, Kevin; Delfanian, Fereidoon
Abstract: Abstract : Material property measurements at the micro-/nanoscale are required for within many materials systems, such as thin-films, coatings, nanostructured materials, and interface/interphase. An innovative approach through micro-/nano-indentation testing with a cylindrical flat-tip indenter and coupled with computer modeling was proposed to characterize the material's elastic–plastic properties. A mechanical model proposed for directly extracting the yield strength of the tested materials, based on the hemi-spherical stress–strain distribution assumption, was analytically derived and numerically validated. Specimens being tested are aluminum alloy, low carbon steel, and alloy steel. A micro-/nano-indentation solid model was constructed and computer modeling was conducted. The load point in the indentation load–depth curve and the modifier for extracting the yield strength were identified through computer modeling and validated by indentation tests. The material properties measured by indentation were compared with tensile tests. The indentation testing errors induced by residual stresses in specimens were investigated by a residual stress measurement system.